2007
DOI: 10.1074/jbc.m609135200
|View full text |Cite
|
Sign up to set email alerts
|

The Recruitment of Phosphatidylinositol 3-Kinase to the E-cadherin-Catenin Complex at the Plasma Membrane Is Required for Calcium-induced Phospholipase C-γ1 Activation and Human Keratinocyte Differentiation

Abstract: Calcium induces epidermal keratinocyte differentiation, but the mechanism is not completely understood. We have previously demonstrated that calcium-induced human keratinocyte differentiation requires an intracellular calcium rise caused by phosphatidylinositol 3-kinase (PI3K)-dependent activation of phospholipase C-␥1. In this study we sought to identify the upstream signaling pathway necessary for calcium activation of PI3K and its subsequent activation of phospholipase C-␥1. We found that calcium induces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 60 publications
(74 reference statements)
6
102
1
Order By: Relevance
“…Observations in our laboratory indicate that in SKOV3 ovarian carcinoma cells forced to grow in suspension E-cadh expression have increased, possibly contributing to escape from anoikis (Miotti, S, unpublished data). These observations and a recent comment by Ahmed et al (2007), together with the present data, support the notion that EOC cells require E-cadh for growth, and argue against the previously proposed suppressive role of E-cadh in transformed ovarian cells, which behave more similarly to normal cells, that is, keratinocytes (Xie and Bikle, 2007) and Madison Darby canine kidney cells (Pece et al, 1999).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Observations in our laboratory indicate that in SKOV3 ovarian carcinoma cells forced to grow in suspension E-cadh expression have increased, possibly contributing to escape from anoikis (Miotti, S, unpublished data). These observations and a recent comment by Ahmed et al (2007), together with the present data, support the notion that EOC cells require E-cadh for growth, and argue against the previously proposed suppressive role of E-cadh in transformed ovarian cells, which behave more similarly to normal cells, that is, keratinocytes (Xie and Bikle, 2007) and Madison Darby canine kidney cells (Pece et al, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…On cell-cell contact formation, E-cadh has been proposed as a 'relationship molecule' between extra and intracellular environments leading to PI3K/AKT activation in normal cells (Pece et al, 1999;Woodfield et al, 2001). E-cadh-mediated cell-cell contacts induce both associations with the PI3K complex and the phospholipase C-g activation in keratinocytes, thus leading to keratinocyte differentiation (Xie and Bikle, 2007). By contrast, in tumor cells, E-cadh expression is lost and E-cadh ectopic expression inhibits invasiveness and growth in a cell-cell adhesion-independent manner (Wong and Gumbiner, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in extracellular Ca 2 ϩ concentration activates a Ca 2 ϩ -sensing receptor (CaR), a G-protein-coupled receptor (Tu et al, 2001), and causes a rapid and sustained increase in intracellular Ca 2 ϩ concentration (Sharpe et al, 1989). This intracellular increase in Ca 2 ϩ concentration is linked to activation of phospholipase C and inositol phospholipid turnover and the production of both diacylglycerol and inositol 1,4,5-trisphosphate (IP3; Xie & Bikle 2007), and activation of protein kinase C (PKC) in keratinocytes (Nagao et al, 1989;Sheu et al, 1989). Concerning PKC, it should be noted that PKC appears to play an important role in 272 Y. KITAJIMA dynamic disassembly and assembly also during wound healing (Wallis et al, 2000;Thomason et al, 2012).…”
Section: Signaling Molecules Involved In Regulation Of Desmosome Dynamentioning
confidence: 99%
“…We previously demonstrated that high extracellular calcium triggers differentiation of keratinocytes by inducing the formation of the p120-catenin-dependent E-cadherinbeta-catenin complex [7][8][9] . Lajolo et al 33 showed that mice fed a diet containing 0.12 g calcium glucarate daily had a reduced rate of oral tumours.…”
Section: Discussionmentioning
confidence: 99%